Lanthanide cation-templated synthesis of rotaxanes. - Zapata, F; Blackburn, O; Langton, M; Faulkner, S; Beer, P (2013)
The first lanthanide cation-templated synthesis of an interlocked structure is demonstrated through an interpenetrated assembly between a pyridine N-oxide threading component coordinating to a lanthanide cation complexed within a macrocycle. Stoppering of the pseudo-rotaxane assembly allows for preparation of the [2]rotaxane.